An atypical case of giant intradiploic epidermoid tumor - Dua, Sanjeev; Dhar, Anil; Singh, Hershdeep; Katyar, Vikrant; Ambastha, Rooma; Shukla, Aditi (International Journal of Health Sciences, 2022)
Intradiploic epidermoid tumors are uncommon and giant epidermoid with dural involvement is scarcer. We report a unique case of a giant frontal epidermoid tumor presenting without typical features of swelling or bulge in scalp. A 61-year-old male presented with the complaints of forgetfulness and headache. Contrast magnetic resonance imaging brain revealed a large left frontal epidermoid tumor. A tumor measuring 13 × 11 × 4 cm, involving the dura but sparing the brain parenchyma, was excised through left frontal craniotomy. Such a presentation of giant epidermoid tumor with dural involvement is highly unusual. Complete surgical excision is the final aim and vigilant follow-up for recurrence is a must.